An aqueous zinc ion battery electrolyte additive and electrolyte containing the additive and applications thereof
Patent Information
- Application Number
- CN202310898781.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-07-21
AI Technical Summary
Aqueous zinc-ion batteries suffer from zinc dendrite growth, hydrogen evolution, and corrosion at the negative electrode/electrolyte interface, leading to irreversibility and reduced energy efficiency. Existing additives require large amounts, resulting in increased internal resistance and reduced energy efficiency.
Pyridoxine is used as an electrolyte additive. By chelating and coordinating with zinc ions, it inhibits the growth of zinc dendrites and forms a reversible adsorption layer, thereby improving the stability and safety of the battery.
It effectively inhibits zinc dendrite formation, improves battery cycle stability and lifespan, reduces the risk of hydrogen evolution corrosion, enhances battery safety and reversibility, and is low-cost and environmentally friendly.
Smart Images

Figure CN116995312B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aqueous energy storage battery technology, specifically relating to an additive for aqueous zinc-ion battery electrolyte, an electrolyte containing the additive, and their applications. Background Technology
[0002] As the world accelerates its energy transition from traditional fossil fuels to clean secondary energy sources, energy storage batteries are playing an increasingly important role, especially lithium-ion batteries, which currently dominate the energy storage market and are widely used in smartphones, wearable devices, and electric vehicles. However, the scarcity of lithium resources, high cost, and the flammability and explosiveness of organic electrolytes limit the long-term development of lithium-ion batteries. In contrast, aqueous zinc-ion batteries show broad development and application prospects due to their low cost, high safety, high theoretical capacity, and large-scale application. However, aqueous zinc-ion batteries also face many challenges during battery storage and operation. Especially at the negative electrode / electrolyte interface, since the zinc negative electrode is directly exposed to the aqueous electrolyte, the tip effect and two-site diffusion cause zinc to preferentially grow in the form of dendrites. At the same time, the thermodynamic instability of zinc metal makes the battery inevitably suffer from hydrogen evolution and corrosion. In addition, zinc ions in the electrolyte mainly exist in the form of solvated structures, which leads to slow ion charge transfer kinetics and requires a large amount of energy consumption during desolvation. In summary, these problems significantly reduce the reversibility and energy efficiency of batteries, and may even cause short circuits and swelling and rupture.
[0003] To address these issues, various modification strategies have been proposed, such as constructing surface coatings, designing negative electrode structures, and using high-concentration electrolytes. However, these methods are not only complex and costly, but also yield limited results. In contrast, introducing additives into the electrolyte is not only simple to implement but also significantly enhances battery stability and extends battery life, making it an important approach to solving the negative electrode / electrolyte interface problem. Therefore, additive optimization strategies are highly favored by researchers. However, most proposed electrolyte additives currently use large quantities, which leads to increased battery internal resistance and zinc nucleation overpotential, resulting in reduced battery efficiency. Summary of the Invention
[0004] To address the above problems, this invention provides an aqueous zinc-ion battery electrolyte additive, an electrolyte containing the additive, and their applications.
[0005] The technical solution adopted in this invention is:
[0006] An aqueous zinc-ion battery electrolyte is composed of a solvent, an electrolyte, and electrolyte additives.
[0007] Furthermore, in the aforementioned aqueous zinc-ion battery electrolyte, the electrolyte additive is pyridoxine, whose structural formula is as follows:
[0008]
[0009] Furthermore, the concentration of the electrolyte additive is 0.5-2 g / L.
[0010] Furthermore, in the aforementioned aqueous zinc-ion battery electrolyte, the solvent is deionized water.
[0011] Furthermore, the deionized water is ultrapure water with a resistance of 18-25 MΩ.
[0012] Furthermore, in the aforementioned aqueous zinc-ion battery electrolyte, the electrolyte is zinc sulfate.
[0013] Furthermore, the concentration of the added electrolyte is 1–3 mol / L.
[0014] The above-mentioned aqueous zinc-ion battery electrolyte is used in aqueous zinc-ion batteries or zinc-ion electrochemical energy storage devices.
[0015] The beneficial effects of this invention are as follows:
[0016] 1. The electrolyte additive provided by this invention contains a polar hydroxyl group, which can chelate and coordinate with zinc ions to disrupt the solvation sheath of zinc ions. This alleviates side reactions such as hydrogen evolution and corrosion caused by the decomposition of released bound water during desolvation. To a certain extent, it can prevent problems such as battery swelling and leakage during use, improve battery safety, and enhance battery cycle stability and battery device lifespan.
[0017] 2. The electrolyte additive provided by this invention has a good coordination effect on zinc metal and can spontaneously adsorb onto the surface of the negative electrode to form a reversible adsorption layer. The adsorption layer can inhibit the two-dimensional diffusion of zinc ions, making the zinc nucleation and growth sites more uniform, thereby inhibiting the formation of dendrites. To a certain extent, this can prevent the occurrence of battery short circuits.
[0018] 3. The electrolyte additive provided by this invention is characterized by its low price, safety, environmental friendliness, and wide applicability. It can improve the cycle stability and lifespan of aqueous zinc-ion batteries.
[0019] 4. The electrolyte provided by this invention has inherent advantages such as low price, safety, environmental friendliness, simple preparation method, and wide applicability. It has significant application prospects and research value in zinc-ion batteries and other potential new energy battery fields. Attached Figure Description
[0020] Figure 1 The XRD patterns are of the negative electrode surface products in different electrolyte systems provided in Embodiment 1 of the present invention.
[0021] Figure 2 The images show SEM images of the negative electrode surface products in different electrolyte systems provided in Example 1 of this invention, where a is a 2M ZnSO4+1g / L PN symmetric cell and b is a 2M ZnSO4 symmetric cell.
[0022] Figure 3 This is a comparison chart of charge-discharge curves of Zn||Zn symmetric batteries in different electrolyte systems provided in Embodiment 1 of the present invention.
[0023] Figure 4 This is a comparison of the coulombic efficiency-cycle number curves of Zn||Cu half-cells in different electrolyte systems provided in Example 2 of the present invention.
[0024] Figure 5 Zn||NH4V4O in different electrolyte systems provided in Example 3 of the present invention 10 Comparison of constant current charge and discharge curves for the entire battery. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0026] Example 1
[0027] (I) Preparation method of battery electrolyte
[0028] 1) Preparation of 2 mol / L zinc sulfate solution: Use an ultrapure water system to obtain ultrapure water with a resistance of 18 MΩ as the solvent, add zinc sulfate heptahydrate powder to the ultrapure water and stir to dissolve, so as to prepare a 2 mol / L zinc sulfate aqueous solution.
[0029] 2) Prepare a zinc sulfate mixed solution containing 1 g / L pyridoxine as the electrolyte: Take a 2 mol / L zinc sulfate aqueous solution, add pyridoxine to it and stir to dissolve, to obtain a zinc sulfate mixed solution containing 1 g / L pyridoxine, which can be used as the electrolyte.
[0030] (II) Preparation methods of positive and negative electrode plates and separators for batteries
[0031] 1) Preparation of positive and negative electrode sheets: High-purity zinc foil (99.99%) with a thickness of 0.1 mm was polished with 2000-grit sandpaper, placed in anhydrous ethanol solution, sonicated for 5 min, and then naturally dried in air. It was then cut into circular sheets with a diameter of 12 mm.
[0032] 2) Preparation of diaphragm: Cut the glass fiber diaphragm into round pieces with a diameter of 16mm.
[0033] (III) Assembly of Zn||Zn symmetric cells
[0034] The button battery used in this embodiment is model CR2032.
[0035] Cut zinc foil was used as the positive and negative electrodes for the button cell. First, the positive electrode was placed in the positive electrode casing, then a glass fiber separator was added, followed by the addition of 160 μL of a zinc sulfate solution containing 1 g / L pyridoxine. The negative electrode was then placed on top of the separator, followed by a spacer and a spring. Finally, the negative electrode casing was closed, and the battery was sealed using a battery packaging machine. This yielded a symmetrical battery using a zinc sulfate solution containing pyridoxine as the electrolyte, labeled as a 2M ZnSO4+1g / LPN symmetrical battery.
[0036] Comparative Example 1 – A symmetrical cell was obtained using a 2 mol / L zinc sulfate aqueous solution as the electrolyte. The assembly method was the same as above, except that a zinc sulfate aqueous solution was used as the electrolyte, and it was labeled as a 2M ZnSO4 symmetrical cell.
[0037] (iv) Testing and Characterization
[0038] The symmetrical battery assembled in this embodiment has a capacity of 1 mA / cm². -2 Current density and 1mAh cm -2 After cycling for 200 hours at the area capacity, Figure 1 The XRD pattern of the products on the negative electrode surface is shown. Compared with the control sample, no basic zinc sulfate byproduct was generated on the negative electrode surface using pyridoxine, indicating that pyridoxine inhibited side reactions such as hydrogen evolution and corrosion. Figure 2 Image a is a SEM image of the negative electrode surface after 200 hours of cycling in a symmetrical battery using pyridoxine. The negative electrode surface is smooth and flat, with no dendrite formation, indicating that pyridoxine inhibits dendrite formation. Figure 2 b is a SEM image of the negative electrode surface of the control sample. The zinc foil is rough and porous, which is significantly different from the sample using pyridoxine additive. Figure 3 It is a symmetrical cell at 1 mAcm -2 Current density and 1mAh cm -2 The charge-discharge performance graphs at the areal capacity show that the battery with added pyridoxine achieved a cycle life of 2800 hours, significantly higher than the 68 hours of the control sample. This indicates that pyridoxine substantially improves the battery's stability.
[0039] Example 2
[0040] (I) Preparation method of battery electrolyte
[0041] 1) Preparation of 2 mol / L zinc sulfate solution: Use an ultrapure water system to obtain ultrapure water with a resistance of 18 MΩ as the solvent, add zinc sulfate heptahydrate powder to the ultrapure water and stir to dissolve, so as to prepare a 2 mol / L zinc sulfate aqueous solution.
[0042] 2) Prepare a zinc sulfate mixed solution containing 1 g / L pyridoxine as the electrolyte: Take a 2 mol / L zinc sulfate aqueous solution, add pyridoxine to it and stir to dissolve, to obtain a zinc sulfate mixed solution containing 1 g / L pyridoxine, which can be used as the electrolyte.
[0043] (II) Preparation methods of positive and negative electrode plates and separators for batteries
[0044] 1) Preparation of positive electrode sheet: Wipe the copper foil with a thickness of 0.002mm with anhydrous ethanol, and after it is naturally dried, cut it into a circular sheet with a diameter of 12mm.
[0045] 2) Preparation of negative electrode sheet: High-purity zinc foil (99.99%) with a thickness of 0.1 mm was polished with 2000-grit sandpaper, placed in anhydrous ethanol solution, sonicated for 5 min, and then naturally dried in air. Afterwards, it was cut into circular sheets with a diameter of 12 mm.
[0046] 3) Preparation of diaphragm: Cut the glass fiber diaphragm into circular pieces with a diameter of 16mm.
[0047] (III) Assembly of Zn||Cu half-cell
[0048] The button battery used in this embodiment is model CR2032.
[0049] First, place the positive electrode sheet into the positive electrode shell, then place the glass fiber separator, and then drop in 160 μL of a zinc sulfate mixed solution containing 1 g / L pyridoxine. Next, place the negative electrode sheet on top of the separator, followed by the gasket and spring sheet. Finally, close the negative electrode shell and seal the battery using a battery packaging machine. This yields a half-cell with a zinc sulfate mixed solution containing pyridoxine as the electrolyte, labeled as a 2M ZnSO4+1g / L PN half-cell.
[0050] Comparative Example 2 – A half-cell was obtained using a 2 mol / L zinc sulfate aqueous solution as the electrolyte. The assembly method was the same as above, except that a zinc sulfate aqueous solution was used as the electrolyte, and it was labeled as a 2M ZnSO4 half-cell.
[0051] (iv) Battery performance testing
[0052] The half-cell assembled in this embodiment has a capacity of 5 mA / cm². -2 Current density and 1mAh cm -2 Constant current charge-discharge tests were performed on the area capacity. Figure 4The corresponding charge-discharge performance graphs show that the battery remained stable after 650 cycles with the addition of pyridoxine, achieving an average coulombic efficiency of 99.68%, while the comparative battery failed completely after only 76 cycles. This indicates that pyridoxine significantly enhances the battery's reversibility.
[0053] Example 3
[0054] (I) Preparation method of battery electrolyte
[0055] 1) Preparation of 2 mol / L zinc sulfate solution: Use an ultrapure water system to obtain ultrapure water with a resistance of 18 MΩ as the solvent, add zinc sulfate heptahydrate powder to the ultrapure water and stir to dissolve, so as to prepare a 2 mol / L zinc sulfate aqueous solution.
[0056] 2) Prepare a zinc sulfate mixed solution containing 1 g / L pyridoxine as the electrolyte: Take a 2 mol / L zinc sulfate aqueous solution, add pyridoxine to it and stir to dissolve, to obtain a zinc sulfate mixed solution containing 1 g / L pyridoxine, which can be used as the electrolyte.
[0057] (II) Preparation methods of positive and negative electrode plates and separators for batteries
[0058] 1) Preparation of the positive electrode: 1.170 g of NH4VO3 was dissolved in 35 mL of deionized water, forming a yellow solution at 80 °C. Then, 1.891 g of H2C2O4·2H2O was added to the solution under magnetic stirring until the solution turned dark green. The solution was transferred to a 50 mL Teflon-lined container and stored in an oven at 140 °C for 48 h. After the sample cooled naturally to room temperature, the product was collected, repeatedly washed by centrifugation with deionized water, and finally freeze-dried. The NH4VO3... 10 Acetylene black and PVDF were mixed in a mass ratio of 7:2:1, an appropriate amount of NMP solvent was added and the mixture was ground into a slurry. The slurry was then evenly coated onto carbon paper and placed in a vacuum drying oven. After 12 hours, the paper was removed and cut into round pieces with a diameter of 12 mm.
[0059] 2) Preparation of negative electrode sheet: High-purity zinc foil (99.99%) with a thickness of 0.1 mm was polished with 2000-grit sandpaper, placed in anhydrous ethanol solution, sonicated for 5 min, and then naturally dried in air. Afterwards, it was cut into circular sheets with a diameter of 12 mm.
[0060] 3) Preparation of diaphragm: Cut the glass fiber diaphragm into circular pieces with a diameter of 16mm.
[0061] (III) Zn||NH4V4O 10 All-battery assembly
[0062] The button battery used in this embodiment is model CR2032.
[0063] First, place the positive electrode sheet into the positive electrode shell, then place the glass fiber separator, and then drop in 160 μL of a zinc sulfate mixed solution containing 1 g / L pyridoxine. Next, place the negative electrode sheet on top of the separator, followed by the gasket and spring sheet. Finally, close the negative electrode shell and seal the battery using a battery packaging machine. This yields a full cell with a zinc sulfate mixed solution containing pyridoxine as the electrolyte, labeled as a 2M ZnSO4+1g / L PN full cell.
[0064] Comparative Example 3 – A full cell was obtained using a prepared 2 mol / L zinc sulfate aqueous solution as the electrolyte. The assembly method was the same as above, except that a zinc sulfate aqueous solution was used as the electrolyte, and it was labeled as a 2M ZnSO4 full cell.
[0065] (iv) Battery performance testing
[0066] The full battery assembled in this embodiment has a capacity of 5Ag. -1 Long-cycle performance testing was conducted on the current density. Figure 5 These are the corresponding long-cycle performance curves. After using pyridoxine, the full cell cycled stably for 1500 cycles, maintaining a capacity retention of 73.2% and an average coulombic efficiency of 99.92%. In contrast, the comparative full cell showed significant fluctuations in coulombic efficiency and discharge specific capacity in the later stages of cycling, with a capacity retention of only 22.4% and an average coulombic efficiency of 99.52% after 1500 cycles. This demonstrates that pyridoxine enhances the stability of the full cell, indicating the practical applicability of this additive.
[0067] Example 4
[0068] (I) Preparation method of battery electrolyte
[0069] 1) Preparation of 2 mol / L zinc sulfate solution: Use an ultrapure water system to obtain ultrapure water with a resistance of 18 MΩ as the solvent, add zinc sulfate heptahydrate powder to the ultrapure water and stir to dissolve, so as to prepare a 2 mol / L zinc sulfate aqueous solution.
[0070] 2) Prepare zinc sulfate mixed solutions containing different concentrations of pyridoxine: Take 2 mol / L zinc sulfate aqueous solution and add different masses of pyridoxine to it to prepare electrolytes containing pyridoxine concentrations of 0.50 g / L, 1.00 g / L, 1.50 g / L and 2.00 g / L respectively.
[0071] (II) Preparation methods of positive and negative electrode plates and separators for batteries
[0072] 1) Preparation of positive and negative electrode sheets: High-purity zinc foil (99.99%) with a thickness of 0.1 mm was polished with 2000-grit sandpaper, placed in anhydrous ethanol solution, sonicated for 5 min, and then naturally dried in air. It was then cut into circular sheets with a diameter of 12 mm.
[0073] 2) Preparation of diaphragm: Cut the glass fiber diaphragm into round pieces with a diameter of 16mm.
[0074] (III) Assembly of Zn||Zn symmetric cells
[0075] The button battery used in this embodiment is model CR2032.
[0076] Zinc foil was used as the positive and negative electrodes of the button cell. First, the positive electrode was placed in the positive electrode casing, followed by a glass fiber separator. Then, 160 μL of a mixed solution of zinc sulfate containing different concentrations of pyridoxine was added. Next, the negative electrode was placed on top of the separator, followed by a spacer and a spring. Finally, the negative electrode casing was closed, and the battery was sealed using a battery packaging machine, resulting in a symmetrical battery using a zinc sulfate mixed solution containing pyridoxine as the electrolyte.
[0077] (iv) Battery performance testing
[0078] The symmetrical battery assembled in this embodiment operates at 1 mA cm⁻¹. -2 Current density and 1mAh cm -2 Constant current charge-discharge tests were conducted at the area capacity, and the test results are shown in Table 1.
[0079] Table 1 Cycle life of symmetric cells containing different concentrations of pyridoxine
[0080] concentration 0 0.5g / L 1g / L 1.5g / L 2g / L Cycle life 28h 186h 2800h 1205h 580h
[0081] As shown in Table 1, the zinc sulfate battery electrolyte containing different concentrations of pyridoxine additives of the present invention can significantly increase the cycle life of aqueous zinc-ion symmetric batteries. In particular, when the concentration of pyridoxine additive is 1 g / L, the cycle life of the battery reaches a maximum value.
Claims
1. An additive for an aqueous zinc-ion battery electrolyte, characterized in that, The electrolyte additive is pyridoxine, and the concentration of the electrolyte additive is 0.5-2 g / L.
2. An aqueous zinc-ion battery electrolyte, characterized in that, The aqueous zinc-ion battery electrolyte is composed of a solvent, an electrolyte, and an electrolyte additive; the electrolyte additive is pyridoxine, and the concentration of the electrolyte additive is 0.5-2 g / L.
3. The aqueous zinc-ion battery electrolyte according to claim 2, characterized in that, The solvent is deionized water.
4. The aqueous zinc-ion battery electrolyte according to claim 3, characterized in that, The deionized water is ultrapure water with a resistance of 18-25 MΩ.
5. The aqueous zinc-ion battery electrolyte according to claim 2, characterized in that, The electrolyte is zinc sulfate.
6. The aqueous zinc-ion battery electrolyte according to claim 5, characterized in that, The concentration of the added electrolyte is 1–3 mol / L.
7. The application of the aqueous zinc-ion battery electrolyte according to any one of claims 2-6 in an aqueous zinc-ion battery.
8. The application of the aqueous zinc-ion battery electrolyte according to any one of claims 2-6 in a zinc-ion electrochemical energy storage device.
Citation Information
Patent Citations
Polymer ionic electrolytes
CN101171717A
Electrolyte additive for aqueous zinc ion battery and application of electrolyte additive
CN115051047A
